A Survey of the Sand Fly Species and Comparing them with the Rates of Cutaneous Leishmaniasis (Baghdad Boil) in Different Habitats of Kut City- Wasit Province - Rhadi Mahran Mohsan; Khais Muri Laabusi AL-Aaidi (Indian Journal of Forensic Medicine & Toxicology, 2021)
The study was carried out in different habitats of Kut city (the center of Wasit governorate) during the periodfrom 1 January to the end of December 2020. It was included a survey of sand fly species that carry theparasites that cause cutaneous leishmaniasis. The results were showed to three types of sand flies (Phlebotomuspapatasi, Sergentomiya sintoni and Phlebotomus sergenti), (67.1, 21.4 and 11.3%), respectively. The studyshowed to find 214 cases of cutaneous leishmaniasis, as the Al-Kut District Center recorded the highestrate of infection, reached 30% (65 cases). While regions of Al-Battar village, Al-Karimiyyah and Al-Jamaaneighborhood recorded 9% (2 cases) for each, which is the lowest rate. The infection rate in Novemberreached 24.7% (53 cases), which is the highest rate, while July was 1.40 % (3 cases), which is the lowest rateof infection. The study was indicated that males are more susceptible to sand fly bites, with rate 55.6%, whilethe rate of targeting of females is 44.3%. The study showed that the rate of sand fly infestation for childrenage of (1-5) years was 25.2%, which is the highest, while its injury rate in age (61-65) years reached 0.46%,which is the lowest rate.